Genetic divergence analysis for qualitative and quantitative traits in groundnut (Arachis hypogaea L.): GENETIC DIVERGENCE ANALYSIS FOR QUALITATIVE AND QUANTITATIVE TRAITS IN GROUNDNUT - S R YADAV,; S B S TIKKA,; A H RATHOD,; S S PATADE,; C N PATIL,; P O VAGHELA, (Journal of Oilseeds Research, 2014)
In the present investigation, 60 genotypes of groundnut were grouped into 12 different clusters. D2analysis indicated existence of wider genetic variability in the population of sixty genotypes which were grouped in twelve clusters, based on their inter clusters distance. The maximum inter-cluster distance was found between cluster III and X carrying one and two genotypes from each cluster respectively followed by that between V and X and cluster III and XII. The minimum inter-cluster distance was observed between cluster VII and XI. The minimum intra-cluster distance (D) was found in cluster II which includes eight genotypes. Cluster III showed high genetic divergence with cluster X followed by cluster V. Therefore it is advisable to make crossing between the genotypes from cluster I with cluster X, cluster III, cluster V and cluster VIII for the generation of wide spectrum genetic variability and isolation of transgressive segregants for enhancement of pod yield in groundnut.